Ce effect on the selective catalytic reduction of NO with CH4 on Pd-mordenite in the presence of O2 and H2O - Costilla, Ignacio Oscar (2011)
The activity, selectivity and stability of Pd/H-MOR and Ce-Pd/H-MOR catalysts for the selective catalytic reduction of NO with CH 4 (SCR-CH 4 ) were studied in O 2 excess (4.1%) in the absence and presence of H 2 O (5%). The reaction was carried out in a 300-650 °C temperature range with a S.V. of ≅33,000 h -1 . The characterization of fresh and used catalysts by FTIR spectroscopy of adsorbed CO and NO showed that the loss of NO conversion in H 2 O presence was due to a decreasing concentration of Pd 2+ sites and to the parallel formation of PdO particles that enhanced CH 4 combustion under dry conditions. This behavior was modified by Ce addition. Under wet conditions the Ce-Pd/H-MOR catalyst was very active (X NO = 76% at 550 °C), selective (100% of N 2 ) and stable. The FTIR spectrum of CO adsorbed on used samples demonstrated that Ce inhibited the transformation of active Pd 2+ into PdO particles. However, Ce presence also enhanced CH 4 combustion under wet conditions. At low temperatures (<500 °C) H 2 O presence inhibited N 2 O formation and 90% selectivity to N 2 , which improved with Ce addition, was obtained.